Gastric mucosal proteomic analysis reveals the role of the TGF-β signaling pathway in gastritis associated with Helicobacter pylori infection - Zhu, Chengjie; Xiong, Lijuan; He, Yun; Sun, Chaoqin; Mo, Fei (Frontiers in Microbiology, 2025)
Helicobacter pylori (H. pylori) infection induces chronic inflammation in the gastric mucosa. There is a close relationship between Th17/Treg cell imbalance and adverse outcomes associated with H. pylori infection. The differentiation and development of both Th17 and Treg cells require the regulatory involvement of TGF-β. However, the regulatory role of the TGF-β signaling pathway in H. pylori-induced gastritis remains unclear. This study aimed to investigate the impact of H. pylori infection on the expression of TGF-β pathway proteins in patients with chronic gastritis, as well as the changes in Th17 and Treg cells and their cytokine expression levels. In this study, gastric mucosal proteomic analysis revealed that differentially expressed proteins were enriched in signaling pathways, such as TGF-β, mitogen-activated protein kinase (MAPK), and Th17. Experiments demonstrated that mRNA levels of TGF-β1 and TAK1, along with their protein expression, were increased in both the peripheral blood and gastric mucosa of H. pylori-infected gastritis patients. Compared to the negative control group, H. pylori-infected gastritis patients showed elevated levels of Th17 and Treg cell transcription factors (RORγt and forkhead box protein 3 (Foxp3) mRNA) in both peripheral blood and gastric mucosa. Additionally, there was an increase in IL-17 and Foxp3 protein expression in the gastric mucosa along with elevated levels of IL-17 and IL-10 in peripheral blood. Animal experiments revealed a decreased ratio of Th17/Treg in H. pylori-infected gastritis mice. We hypothesize that H. pylori infection may contribute to gastric mucosal inflammatory responses by activating the TGF-β signaling pathway and disrupting the immune balance between Th17 and Treg cells during inflammation. These findings provide new strategies for the prevention and treatment of H. pylori-induced gastritis.